Domain Selectivity in BiFeO3 Thin Films by Modified Substrate Termination. (21st March 2016) - Solmaz, Alim; Huijben, Mark; Koster, Gertjan; Egoavil, Ricardo; Gauquelin, Nicolas; Van Tendeloo, Gustaaf; Verbeeck, Jo; Noheda, Beatriz; Rijnders, Guus
Abstract : Ferroelectric domain formation is an essential feature in ferroelectric thin films. These domains and domain walls can be manipulated depending on the growth conditions. In rhombohedral BiFeO3 thin films, the ordering of the domains and the presence of specific types of domain walls play a crucial role in attaining unique ferroelectric and magnetic properties. In this study, controlled ordering of domains in BiFeO3 film is presented, as well as a controlled selectivity between two types of domain walls is presented, i.e., 71° and 109°, by modifying the substrate termination. The experiments on two different substrates, namely SrTiO3 and TbScO3, strongly indicate that the domain selectivity is determined by the growth kinetics of the initial BiFeO3 layers. Abstract : Growth of the BiFeO3 thin films is shown to depend on the atomic termination of the SrTiO3 and TbScO3 substrates. Interface engineering with a single SrO layer on substrate surfaces enables the control of domain ordering and selectivity between 71° and 109° domain walls. Underlying mechanism is claimed to be growth dynamic during the initial phase of growth.